Socio-demography factors for level of competency among rural administrators: the case of Peninsular Malaysia - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva (EuroJournals, 2009)
The purpose of this study is to examine the rural administrators which is Village Development and Security Comittee level of competency and socio demographic factor that affect it. This study used quantitative method where instrument was designed based on the objectives of the study. This study was conducted in three zones located in Peninsular Malaysia. Eighteen villages listed in Village Vission Movement (VVM) were selected from the three zones. A total of 235 respondents were chosen for this study. Overall, members of Village Development and Security Comittee had high level of competency. This study found that village grade had significant difference with competency level while age had positive correlation with level of JKKK members competency. Based on the simple linear regression done, age was the highest contributor to the competency level.